Bulozi under the Luyana Kings : Political Evolution and State Formation in Pre-Colonial Zambia. - Mainga, Mutumba (Bookworld Publishers, 2010)
Bulozi under the Luyana Kings is a study of the Lozi Kingdom in Western Zambia in the pre-colonial period. The study traces the origins of the Luyana and the Lozi people; the founding of the Luyana Central Kingship and the invasion by the Makololo in the mid-nineteenth century; and ends with the study of the Lozi response to European intrusion at the end of the nineteenth and early twentieth centuries. Bulozi under the Luyana Kings was first published in 1973 by Longman, London. After wide consultations at home and abroad, the book is now republished in its original form.